Hypertensive Disorders of Pregnancy in a Military Hospital Birth Cohort - Jimi Francis; Karla Waller; Amber Wilson; Darby Dickton (Mary Ann Liebert, 2022)
Background: Hypertensive disorders of pregnancy (HDP) are risk factors for maternal and fetal complications with long-term sequelae for mother and children. HDP are not clearly understood; however, there appears to be a relationship with maternal weight gain. The effects of maternal weight gain and pregnancy outcomes, including HDP, are understudied. Few studies have assessed maternal weight gain in service-connected women and its effects on HDP. This study aimed to evaluate the relationship between blood pressure and birth outcomes in women who delivered their infants at a military hospital. Methods: This birth cohort study included all patients admitted to a military hospital for delivery over a 12-month period. Data were analyzed for hypertensive disorders, maternal weight gain, delivery type, infant maturity, and infant weight at delivery. Results: Of the 1,018 participants, 186 were diagnosed with HDP with no statistical difference observed for maternal age. The hypertensive group had higher mean weight gain. More patients in the hypertension group delivered at term with lower mean birth weight. The rate of small-for-gestational age infants was higher in the HDP group (p?<?0.001). Discussion: The rate of HDP in this cohort of military members and dependents was 18.3%, which was similar to the 19% rate reported for a southern US hospital, but higher than in other regions of the United States. This evidence indicates that HDP are increasing, and maternal/infant morbidity was affected by hypertension in this study.